Letter to the Editor concerning “Impact of preoperative mental health disorders on postoperative outcomes in patients with adolescent idiopathic scoliosis undergoing surgery” by Vallee EK, et al. (Spine Deformity [2026]: doi:10.1007/s43390-026–01288-z) - Kishankumar Mahida; Snehal Rajendra Jagtap (Spine Deformity, 2026)
PURPOSE OF REVIEW: Oral potentially malignant disorders (OPMDs) comprise a heterogeneous group of lesions with a variable risk of progression to oral squamous cell carcinoma (OSCC). Although conventional risk assessment relies primarily on clinical and histopathological features, increasing evidence suggests that the local oral microenvironment may also influence malignant transformation. This narrative review examines the potential role of periodontitis as a modulator of OPMD progression, with particular emphasis on the underlying biological mechanisms and clinical implications. A targeted literature search was conducted in PubMed/MEDLINE, Scopus/EMBASE, and Web of Science for studies published between January 2000 and March 2026. RECENT FINDINGS: Available evidence suggests that periodontitis may promote a pro-tumorigenic oral microenvironment through the interconnected effects of chronic inflammation, microbial dysbiosis, and metabolic alterations. These processes may enhance epithelial proliferation, genomic instability, immune evasion, and field cancerization, potentially facilitating the progression of OPMDs to OSCC. Although direct longitudinal and interventional evidence remains limited, converging mechanistic, biological, and epidemiological findings support the hypothesis that periodontal disease may contribute to early oral carcinogenic processes. Periodontitis may represent an underrecognized component of oral cancer risk, particularly in patients with OPMDs. Incorporating periodontal assessment into their clinical management may support more comprehensive risk stratification. Although causality has not been established, controlling periodontal inflammation and dysbiosis may offer a potential preventive strategy. Further longitudinal and interventional studies are required to determine the clinical relevance of this association.